Roots of 20th-Century Western Counterculture: From Guillem Rovirosa’s Catalonia to Its Antipode - José Andrés-Gallego (Religions)
The point of departure for this essay is the first part of the life of Guillem Rovirosa (1915–1934), before he became one of the most important social activists in post-war Spain. During those years he abandoned his Catholic faith and, accompanied by a few friends, embarked on a journey of exploration through Esperanto, naturism, spiritualism, and theosophy. This essay proposes the application of comparative microhistory to religious sociology. The author has sourced similar combinations from around the world in the same period and concludes that this melting pot was not unique. Quite the contrary, from Europe to the Far East, many people underwent similar experiences, usually of a countercultural nature and often linked to the idea of anti-authoritarianism and to its possible religious foundations.